Radical Imagination - in the Making of the World : A Glimpse into the Works of Hannah Arendt and Saidiya V. Hartman - Popal, Mariam (News from The Institute of African Studies at the University of Bayreuth, 2025)
On the work of Hannah Arendt and Saidiya V. Hartman
Keywords: imagination; theory & praxis; critical thinking; archive; canon; critical canon; decolonizing thought